UJI MIKROSKOPIK EKSTRAK ETANOL 96% HERBA CIPLUKAN (Physalis angulata L.) - Istiqomah, Rifqi; Pratiwi, Liza; Luliana, Sri (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Physalis angulata L. is a plant whose extract or infusion has been used by many countries as a popular medicine for the treatment of diseases such as malaria, asthma, hepatitis, dermatitis and rheumatism. The ethanol extract of ciplukan herb has been studied to show non-toxic activity with an LC50 value of more than 1000 ?g / mL so that it is potential to be developed into a dosage form. This study aims to determine the correctness of a sample by identifying its distinctive fragments through microscopic testing. The research method begins with determining the sample to ensure that the plants to be used are appropriate. Then performed microscopic tests and extraction. The results showed that the typical fragments found in the ciplukan herbal simplicia were the transport files, while the yield value of 96% ethanol extract of ciplukan herbs obtained in this study was 2.04%. Keywords: Physalis angulata L., microscopic testing, extraction